Impact of Consumption Values on Consumer Environmental Concern Regarding Green Products: Comparing Light, Average, and Heavy Users’ - Suki, Norazah Mohammed; Suki, Norbayah Mohammed (International Journal of Economics and Financial Issues, 2015)
This study seeks to investigate the association of consumer consumption values (i.e. functional value, social value, and epistemic value) with consumer environmental concern regarding green products among light users, average users, and heavy users. This study applies a quantitative method based on the development of a structured self-administered questionnaire. Data was analyzed via correlation analysis and One-Way Analysis of Variance (ANOVA) utilizing Statistical Package for Social Sciences (SPSS) computer programme version 21. Results revealed that statistically significant differences were observed among the light users, average users and heavy users in terms of functional value, social value, and epistemic value that affect consumer environmental concern regarding green products. The results of this study furnish new momentum for the preceding discoveries on consumer environmental concern regarding green products, which are inadequately covered in the Malaysian context. The results provide important information and encourage companies to put more emphasis on functional value, social value, and epistemic value in order to boost consumer environmental concern regarding green products, which could assist the manufacturers in producing green products that will be readily liked by consumers. Keywords; Green product; Consumption value; Environmental concern; Structural Equation Modelling JEL Classifications: M00